Effect of proning in patients with COVID-19 acute hypoxemic respiratory failure receiving noninvasive oxygen therapy - P B Sryma; Saurabh Mittal; Anant Mohan; Karan Madan; Pawan Tiwari; Sushma Bhatnagar; Anjan Trikha; Ravi Dosi; Shweta Bhopale; Renjith Viswanath; Vijay Hadda; Randeep Guleria; et al. (Lung India, 2021)
Background: Novel coronavirus (SARS-CoV-2) infection is associated with hypoxemic respiratory failure. Mechanical ventilation (MV) is reported to have high mortality in SARS-CoV-2 acute respiratory distress syndrome. We aimed to investigate whether awake prone positioning (PP) can improve oxygenation and prevent intubation when employed early. Methods: This prospective interventional study included proven coronavirus disease 2019 (COVID-19) patients with room air saturation 93% or less. The primary outcome was the rate of intubation between the two groups. The secondary outcomes included ROX index (SpO2/FiO2%/respiratory rate, breaths/min) at 30 min following the intervention, ROX index at 12 h, time to recovery of hypoxemia, and mortality. Results: A total of 45 subjects were included (30 cases and 15 controls) with a mean (standard deviation [SD]) age of 53.1 (11.0) years. The age, comorbidities, and baseline ROX index were similar between the two groups. The median duration of PP achieved was 7.5 h on the 1st day. The need for MV was higher in the control group (5/15; 33.3%) versus prone group (2/30; 6.7%). At 30 min, there was a statistically significant improvement in the mean (SD) ROX index of cases compared with that of the controls (10.7 [3.8] vs. 6.7 [2.6], P < 0.001). No significant adverse effects related to intervention were noted. Conclusion: Awake PP is associated with significant improvement in oxygenation and may reduce the need for MV in subjects with COVID-19.